Comparison of Antioxidant Activity of Methanol Extract of Young and Old Leaves of Avocado (Persea americana Mill.) - Pratiwi, Ambar; Agustina, Devanda Rahma; Febrianti, Novi; Eryati, Eri (Biota, 2024)
Avocado plants (Persea americana Mill.) are widely grown in tropical and subtropical regions. Avocado leaves contain natural antioxidants for traditional medicine. This study aims to determine the total phenolic content, total flavonoids, and antioxidant activity values of young and old avocado leaves, and analyze the relationship between total phenol content and total flavonoids to the antioxidant activity value of avocado leaf methanol extract (Persea americana Mill.). The macerated avocado leaf extract was quantitatively tested for antioxidant activity using the DPPH method and the total phenolic and flavonoid contents were calculated using the Follin-Ciocalteu and Follin-Ciocalteu methods, respectively.The results showed that the highest total phenolic content of old avocado leaves was 1.682,27mg GAE/100g dry weight. The highest total flavonoid content of avocado old leaves was 3.858,96mg QE/100g dry weight. Antioxidant activity of methanol extract of young avocado leaves has a value of IC50 321.32 ± 80.43 ppm and avocado old leaves amounted to 288.54 ± 33.06 ppm. Total flavonoid content was more influential on antioxidant activity, with a correlation coefficient of 0.856